Validation of Reference Genes via qRT-PCR in Multiple Conditions in Brandt’s Voles, Lasiopodomys brandtii - Lin Tian; Yan Chen; Da-Wei Wang; Xiao-Hui Liu (Animals, 2021)
The choice of optimal reference gene is challenging owing to the varied expression of reference genes in different organs, development stages, and experimental treatments. Brandt’s vole (Lasiopodomys brandtii) is an ideal animal to explore the regulatory mechanism of seasonal breeding, and many studies on this vole involve gene expression analysis using quantitative real-time polymerase chain reaction (qRT-PCR). In this study, we used the method of the coefficient of variation and the NormFinder algorithm to evaluate the performance of nine commonly used reference genes Gapdh, Hprt1, β-actin, PPIA, Rpl13a, Tbp, Sdha, Hmbs, and B2M using qRT-PCR in eight different tissues, five developmental stages, and three different photoperiods. We found that all nine genes were not uniformly expressed among different tissues. B2M and Rpl13a were the optimal reference genes for different postnatal development stages in the hypothalamus for males and females, respectively. Under different photoperiods in the hypothalamus, none of the selected genes were suitable as reference genes at 6 weeks postnatal; β-actin and PPIA were the optimal reference genes at 12 weeks postnatal; Hprt1, β-actin, PPIA, Hmbs, and B2M were excellent reference genes at 24 weeks postnatal. The present study provides a useful basis for selecting the appropriate reference gene in Lasiopodomys brandtii.